(untitled) (Journal of Ideas in Health, 2022)
Background: In the absence of effective treatment, coronavirus disease (Covid-19) poses severe risks to public health. This study aimed to explore the knowledge, attitude, and practice towards the COVID-19 pandemic among healthcare workers. Methods: An online approach was adopted to conduct a cross-sectional study from 1st to 31st October 2020 among Iraqi healthcare workers in Anbar Province, west of Iraq. A semi-structured and self-administered questionnaire was recruited to collect the data. The study tool contains four parts sociodemographic, knowledge, attitude, and practice assessment. Multiple Linear regression was performed to test the association between the dependent and the independent variables. SPSS version 16 was used to analyze the data, and the statistical significance level was considered at less than 0.05 p-values. Results: A total of 209 health workers were included in this study. Most of the respondents (54.5%) were Doctors (Physician, dentist, and pharmacist), males (60.8%), married (74.2%), aged less than 45 years (53.1%), urban region (64.6%), with a monthly income of USD 400 and above (61.7%) and 75.1% of them perceived their health good. The mean knowledge, attitude, and practice level of participants were 14.43 (± 2.01), 27.68 (± 2.74), and 4.33 (± 0.97), respectively. In the regression analysis, doctors (P-value = 0.000) aged 45 years and above (P-value=0.008) and urban residents (P-value=0.007) were significantly associated with upper knowledge scores. Female gender (P-value =0.022) was significantly related to positive attitude scores. While married (P-value = 0.038), those with experience of 10 years and above (P-value=0.041) showed better practice. Conclusion: The level of knowledge, attitudes, and practices of healthcare workers in Anbar Province was adequate. However, with the expected new waves of pandemics, the policy of continuous training to update healthcare workers is inevitable to control and prevention of COVID-19.